Synthesis and Spectroscopic Characterization of Two New Thiosaccharinate Salts : Molecular Structure of Bis(triphenylphosphine)iminium thiosaccharinate, PNP(tsac) - Dennehy, Mariana (2007)
We report the synthesis, FTIR, Raman and NMR spectroscopic features of bis(triphenylphosphine)iminium and tetrabutylammonium thiosaccharinates, PNP(tsac) and NBu₄(tsac) (tsac: thiosaccharinate anion, PNP: bis(triphenylphosphine)iminium). The molecular structure of the former compound was determined by X-ray diffraction methods. The salt crystallizes in the monoclinic P2₁/n space group with a = 9.6481(9), b = 29.258(3), c = 13.177(2) Å, β = 97.53(1)°, and Z = 4 molecules per unit cell. Slight but significant changes in the bonding structure of the thiosaccharinate anion as compared with those reported for the neutral molecule are observed.